Serotype distribution and resistance genes associated with macrolide and fluoroquinolone resistance in Streptococcus agalactiae isolates from a hospital in southern Taiwan - Ying-Hsiang Wang; Chyi-Liang Chen; Jiun-Nub Hou; Yi-Rou Wang; Ting-Yu Lin; Mei-Hei Wang; Tsung-Han Yang; Chishih Chu; Cheng-Hsun Chiu (Biomedical Journal, 2015)
Background: Antimicrobial resistance of Streptococcus agalactiae (Group B Streptococcus, GBS) has been emerging worldwide. We aimed to examine the correlation of drug-resistant genes with serotypes and with the mutations of the quinolone resistance-determining region (QRDR) in GBS isolates. Methods: A total of 323 human GBS isolates were collected from a hospital in southern Taiwan. Laboratory investigation included serotyping by a multiplex polymerase chain reaction (PCR) method, antimicrobial susceptibility testing by a disc diffusion method, and mechanism analysis of the resistance to macrolides and fluoroquinolones by PCR and sequencing methods. Results: Multiplex PCR showed that the most prevalent serotypes were Ib, III, V, and VI, mostly isolated from urine. The ermB gene was highly prevalent in serotypes Ib and V and was associated with clindamycin and macrolide resistance. GBS with a serine-to-leucine mutation at codon 81 in GyrA and with a serine-to-phenylalanine or -tyrosine mutation at codon 79 in ParC had a higher minimum inhibitory concentration of levofloxacin than isolates with only an aspartic acid-to-tyrosine mutation at codon 83 (>32 μg/ml vs. 16 μg/ml) in GyrA. Conclusions: The most prevalent GBS serotypes were Ib, III, V, and VI. The ermB and mefE genes carried in serotypes Ib and V were highly associated with the resistance to macrolides and clindamycin. Mutations at codon 79 and codon 83 of ParC were the major determining factors for high-level fluoroquinolone resistance.